ANALYSIS OF APPRAISAL SYSTEM IN THE EDITORIAL ABOUT UIGHUR, MIDLE EAST WITH CHINA - Ninuk Sholikhah Akhiroh (Prasasti: Journal of Linguistics)
Objectivity and neutrality are hard to achieve in journalistic text. Editorial as part of journalistic text functioning to give opinion on certain issues should have its own standard of objectivity and neutrality. This study aimed at describing things, people, or parties involved in an issue carried by an editorial, and explain how the writer behaves and gives an assessment of the things, people, or parties. The study was held in a descriptive-qualitative method using Appraisal Theory to analyze the data taken from the editorial of an Indonesian news website. Research results showed various appraised items in the editorial meaning that there are various things and parties involved in the issue.  The attitude of the writer toward the issue was marked by the domination of negative expressions in affect and judgement, and a dominationn of positive expression in appreciation. The writer used different modes in proposing opinion. From the findings of the research it can be concluded that using proper expressions in showing attitude and providing reliable facts are key to write an ‘objective and neutral’ editorial.